Performance evaluation of asphalt mixture exposed to dynamic water and chlorine salt erosion. (20th March 2019) - Xiong, Rui; Chu, Ci; Qiao, Ning; Wang, Lu; Yang, Fa; Sheng, Yanping; Guan, Bowen; Niu, Dongyu; Geng, Jiuguang; Chen, Huaxin
Highlights: Chlorine salt-water-temperature-load action affects durability of asphalt mixture. Dynamic water-salt erosion apparatus obtains a desirable accelerated simulation. Dynamic water accelerates the chlorine salt erosion to asphalt mixture. Abstract: The salt corrosion environment has direct degradation to durability of asphalt mixture and dynamic water also has an important influence on asphalt pavement performance. In order to evaluate the performance of asphalt mixture exposed to dynamic water and chlorine salt erosion, the asphalt mixture dynamic water-salt erosion apparatus was self-designed and the test parameters were reasonably set for the accelerated simulation of chlorine salt-water-temperature-load coupling action to asphalt mixture under real working conditions. Splitting test (25 °C and −10 °C) was adopted for assessing the performance of asphalt mixture suffered from chlorine salt-water-temperature-load coupling action. Then the grey entropy method was applied to analyze the significance of influencing factors on the performance of asphalt mixture such as dynamic water scouring times, temperature, salt solution concentration. Then the mechanism of performance deterioration of asphalt mixture was explored to some extent. The results show that the process of chlorine salt erosion and deterioration to asphalt mixture is accelerated by dynamic water and is closely related to the concentration and temperature of salt solution. Scouring times is the most significant factor influencing the performance of asphalt mixture exposed to dynamic water and chlorine salt erosion. The crystallization erosion caused by salt solution infiltrating into the voids and cracks of asphalt mixture is an important inducement for the performance deterioration.